Planktonic Microalgae in Recreational Fishponds of the Crato Municipality, Ceará State, Brazil - Góes, Maria Irismã Libório; Nascimento, Karla Jaqueline do; Rangel, Anne Jussara; Ferreira, Renato Juciano; Santos, Tânia Maria Lopes dos; Lacerda, Sírleis Rodrigues (Revista em Agronegócio e Meio Ambiente, 2016)
This study aimed to evaluate the occurring phytoplankton composition in the two recreational fishponds in Crato municipality, south of Ceará. Samples for the study were collected monthly, from June 2012 to March 2013, using plankton net and glass separator (20 ?m), fixed with 4% formalin and deposited in the Botany Laboratory of the assets of Regional University of Cariri, where were made analysis and taxonomic identification. The phytoplankton community proved to be represented by 100 taxa belonging to five divisions: Chlorophyta which contributed 56% of total taxa, followed by Euglenophyta (18%), Cyanobacteria (16%), Bacillariophyta (7%) and Dinophyta (3% ). The Scenedesmaceae family presented the highest number of taxa (19) and Scenedesmus and Desmodesmus genres presented greater number of species. Desmodesmus comunis (Hegewald) Hegewald and Desmodesmus opoliensis (P. Hichter) Hegewald (Chlorophyta) and Aphanocapsa sp. (Cyanobacteria) were classified as dominant and other two named species of Chlorophyta abundant Desmodesmus armatus (R. Chodat) E. Hegewald and Scenedesmus producto-capitatus Schumula. As the frequency 10% were classified as very frequent, 14% frequent and the others too infrequent. 75% had average diversity and the community with equitable distribution of taxa. The set of information made in relation to the phytoplankton community characterized the ecosystems studied from meso to eutrophic. MICROALGAS PLANCTÔNICAS DE PESQUEIROS DO MUNICÍPIO DO CRATO, CEARÁ, BRASIL O presente estudo teve como objetivo avaliar a composição fitoplanctônica ocorrente em dois pesqueiros do município do Crato, Sul do Estado do Ceará. As amostras para o estudo foram coletadas mensalmente, no período de junho de 2012 a março de 2013, utilizando rede e copo separador de plâncton (20µm), fixadas com formol a 4% e depositadas no acervo do Laboratório de Botânica da Universidade Regional do Cariri, onde foram efetuadas análise e identificação taxonômica. A comunidade fitoplanctônica mostrou-se representada por 100 táxons distribuídos em cinco divisões: Chlorophyta, que contribuiu com 56% do total de táxons, seguida de Euglenophyta (18%), Cyanobacteria (16%), Bacillariophyta (7%) e Dinophyta (3%). A família Scenedesmaceae foi a que apresentou maior número de táxons (19) e os gêneros Desmodesmus e Scenedesmus apresentaram maior número de espécies. Desmodesmus comunis (Hegewald) Hegewald e Desmodesmus opoliensis (P. Hichter) Hegewald (Chlorophyta) e Aphanocapsa sp. (Cyanobacteria) foram classificadas como dominantes e outras duas espécies de Chlorophyta denominadas abundantes Desmodesmus armatus (R. Chodat) E. Hegewald e Scenedesmus producto-capitatus Schumula. Quanto à freqüência, 10% foram classificadas como muito frequentes, 14% frequentes e as demais pouco frequentes. 75% apresentaram média diversidade e a comunidade com distribuição equitativa dos táxons. O conjunto de informações levantadas em relação à comunidade fitoplanctônica caracterizou os ecossistemas estudados de meso a eutrófico. PALAVRAS-CHAVE: Cyanobacteria; Diversidade; Fitoplâncton